Translating the “Banana Genome” to Delineate Stress Resistance, Dwarfing, Parthenocarpy and Mechanisms of Fruit Ripening - Dash, Prasanta K.; Rai, Rhitu (Frontiers in Plant Science, 2016)
Evolutionary frozen, genetically sterile and globally iconic fruit “Banana” remained untouched by the green revolution and, as of today, researchers face intrinsic impediments for its varietal improvement. Recently, this wonder crop entered the genomics era with decoding of structural genome of double haploid Pahang (AA genome constitution) genotype of Musa acuminata. Its complex genome decoded by hybrid sequencing strategies revealed panoply of genes and transcription factors involved in the process of sucrose conversion that imparts sweetness to its fruit. Historically, banana has faced the wrath of pandemic bacterial, fungal, and viral diseases and multitude of abiotic stresses that has ruined the livelihood of small/marginal farmers’ and destroyed commercial plantations. Decoding structural genome of this climacteric fruit has given impetus to a deeper understanding of the repertoire of genes involved in disease resistance, understanding the mechanism of dwarfing to develop an ideal plant type, unraveling the process of parthenocarpy, and fruit ripening for better fruit quality. Further, injunction of comparative genomics will usher in integration of information from its decoded genome and other monocots into field applications in banana related but not limited to yield enhancement, food security, livelihood assurance, and energy sustainability. In this mini review, we discuss pre- and post-genomic discoveries and highlight accomplishments in structural genomics, genetic engineering and forward genetic accomplishments with an aim to target genes and transcription factors for translational research in banana.